Academic Senate Minutes 2001-09-13 - Academic Senate:::::::::
Agenda and Minutes approved. Report from the Chair. Senate ByLaw revisions approved. First reading of 120 unit BA report and procedures. First reading for compensation for lecturer's serving on the Senate. Resolution endorsing CFA Teach-In approved. Report on Lifelong Learning Institute from Les Adler. Reports from Provost, Chair-Elect, Statewide Senator, President of Associated Students, APC, EPC, FSAC and SAC.